Assessing an Epidemic: Utility of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition Level 2 Substance Use Screener in Adult Psychiatric Inpatients. Issue 1 (January 2020) - Sullivan, Matthew C.; Strainge, Lauren; Blackmon, Jaime E.; Cruess, Stacy E.; Wheeler, David; Cruess, Dean G.
Abstract: Background: Inpatient psychiatric hospitals provide an important point of care for assessing and stabilizing substance use and for facilitating linkage to appropriate treatment. Toxicology screening provides a key measure of substance use yet may miss many cases of substance use because of variable windows of detection and the limited scope of substances assessed. This study assesses the utility of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM-5 ) Level 2 Substance Use screener as a supplemental tool for identifying substance use by self-report within an inpatient psychiatric hospital setting. Methods: From a larger sample of 97 adult psychiatric inpatients, 60 who underwent drug toxicology testing and completed the DSM-5 screener were assessed. We examined the sensitivity and specificity of the self-report screener in comparison with drug toxicology test results collected by chart review. Results: Sensitivity of the DSM-5 screener varied across substances assessed: The self-report measure identified 100% of individuals who tested positive for opioid use, 83% who tested positive for cannabis use, 50% who tested positive for cocaine use, and 37% who tested positive for benzodiazepine use. The self-report measure also identified 27 instances among 60 participants in which substance use identified by self-report was not detected by toxicology testing. Conclusion: The brief and easily administered DSM-5 Level 2 Substance Use screener shows promise for improving identification of substance use in an inpatient psychiatric hospital setting. This measure may also provide psychiatric inpatient nursing staff with a means of working collaboratively with patients to assess substance use and coordinate appropriate treatment plans.